John Buridan on Moral Skepticism and Acting Well with False or Limited Information - Stöpfgeshoff, Alexander (American catholic philosophical quarterly, 2025)
John Buridan's (c. 1300-1361) influential discussion on the possibility of knowledge concludes that divine deception does not undermine human knowledge. He holds that natural and moral knowledge need not be absolutely evident, but rather evident in a qualified sense. Buridan's response to this skeptical challenge is widely regarded as a milestone in the history of skeptical thought. While Buridan's account of how natural knowledge is possible has attracted considerable scholarly attention, his consideration of how moral knowledge is possible has largely been neglected. In this paper, I argue that Buridan's innovative approach suggests that correct moral decisions can be reached on the basis of practical wisdom, even under conditions of false or limited information.